Radiographic findings in panoramic radiographs of patients attending Kulliyyah of Dentistry, IIUM - Kashmoola, Muhannad Ali; Mustafa, Nazih Shaban; Mohd Ali, Azrul Safuan; Dahlan, Kamal Ammar (Kulliyyah of Dentistry, International Islamic University Malaysia, 2020)
This research was done to study the radiographic finding of the jaws amongst the patients attending at the polyclinic using Orthopanthomograph (OPG). The OPG was taken using the Planmeca Promax 3D and the Planmeca Romexis software (Version 2.1.1.R). The first step was collecting all the OPG images from 1st April 2009 until 31st January 2011. Then, the abnormal radiographs were further divided into 3 groups which were radiolucent, radiopaque and mixed. This classification includes site, size, border, and possible diagnosis as part of the lesion`s appearance. One thousand four hundred and five OPG images were retrieved, 96 images were discarded because of poor quality. The data collected were analyzed statistically by using SPSS Version 16.0. Among 77 abnormal radiographic images, 41 images were radiopaque, 30 images were radiolucent and 6 images were mixed. Out of 77 abnormal images, 34 images that showed bone lesion were from male patients while the rest which was 43 images from female. In conclusion, most of the pathological lesion occur in the mandible.